2015
DOI: 10.1039/c5ra10849g
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress in chemical modification of starch and its applications

Abstract: Starch has received much attention as a promising natural material both in biomedical fields and waste water treatment due to its unique biological and adsorptive properties. Recently, the modification of starch is rapidly developed along with its growing applications. This review focuses on the ways of chemical modification of starch including cross-linking, grafting, esterification, etherification, dual modification and so on, and presents the applications of the modified starch in fields like drug delivery,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
81
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(81 citation statements)
references
References 186 publications
(217 reference statements)
0
81
0
Order By: Relevance
“…According to Zheng, Li, Zhang, and Wang, (2007), the main classes of natural polymers used to produce hydrogels are: i) proteins such as collagen, gelatin, soy, and fish proteins (Zohuriaan-Mehr, Pourjavadi, Salimi, & Kurdtabar, 2009); and ii) carbohydrates such as starch (Chen et al, 2015), cellulose and its derivatives (Bao et al, (Bansal, Sharma, Sharma, Pal, & Malviya, 2011;Cuadri, Bengoechea, Romero, & Guerrero, 2016;Guilherme et al, 2015;Wang, Huang, Kang, & Wang, 2013). Moreover, an interesting raw material for producing hydrogels is the bacterial cellulose.…”
Section: According To the Nature Of The Polymeric Matrixmentioning
confidence: 99%
“…According to Zheng, Li, Zhang, and Wang, (2007), the main classes of natural polymers used to produce hydrogels are: i) proteins such as collagen, gelatin, soy, and fish proteins (Zohuriaan-Mehr, Pourjavadi, Salimi, & Kurdtabar, 2009); and ii) carbohydrates such as starch (Chen et al, 2015), cellulose and its derivatives (Bao et al, (Bansal, Sharma, Sharma, Pal, & Malviya, 2011;Cuadri, Bengoechea, Romero, & Guerrero, 2016;Guilherme et al, 2015;Wang, Huang, Kang, & Wang, 2013). Moreover, an interesting raw material for producing hydrogels is the bacterial cellulose.…”
Section: According To the Nature Of The Polymeric Matrixmentioning
confidence: 99%
“…Chemical modification is introduced to overcome the inherent defects and gain innovation in the utilization of starch. It involves the introduction of various functional groups into starch structure including cationic and anionic group [4].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, physical modification of starch reduces its melting temperature, viscosity, and swelling power and increases its solubility . Further, numerous studies have reported that chemical modification procedures, such as cross‐linking, oxidization, acidification, and esterification, considerably improve the functional properties of starches . Modified starches are widely used for preparing soups, sauces, milk‐based desserts, and deep‐fried products .…”
Section: Introductionmentioning
confidence: 99%